2007
DOI: 10.1111/j.1467-8276.2007.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Fixed Costs, and Location‐Specific Amenities: A Hazard Analysis for a Panel of Males

Abstract: This article presents econometric estimates of the adult working-age male hazard function of interstate migration fitted to data obtained from migration decisions of adult males over a twenty-year period. The results show a strong negative effect of the real wage difference between origin and destination, and of fixed costs associated with a move, on the hazard rate of interstate migration. Farmers and other self-employed males, and males who have school-age children, have unusually low hazard rates of interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
0
8
1
2
Order By: Relevance
“…We find that recent graduates' propensity to leave a metropolitan area increases with decreasing crime rates. This contrasts with results obtained from a recent micro-level study that finds that high crime rates increase the hazard of migrating to another state (Huffman and Feridhanusetyawan 2007). However, our results are not implausible and do not imply that young graduates have a dislike for safe environments.…”
Section: Resultscontrasting
confidence: 99%
“…We find that recent graduates' propensity to leave a metropolitan area increases with decreasing crime rates. This contrasts with results obtained from a recent micro-level study that finds that high crime rates increase the hazard of migrating to another state (Huffman and Feridhanusetyawan 2007). However, our results are not implausible and do not imply that young graduates have a dislike for safe environments.…”
Section: Resultscontrasting
confidence: 99%
“…The most recent analysis was an employment-migration simultaneous equations model conducted at the county level by Eichman et al (2010), which found that "the presence of reserved land decreases annual employment growth rates from 1.75 percent to 1.52 percent" (p. 331) during the decade immediately following implementation (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)). The regional science literature has examined the effects of conservation lands on regional economies in a variety of studies that build off the more general literature linking amenities and regional growth (e.g., Blomquist, Berger, and Hoehn, 1988;Gyourko and Tracy, 1991;Schmidt and Courant, 2006;Huffman and Feridhanusetyawan, 2007;Deller, 2009;Rickman and Rickman, 2011). The conservation literature within regional science has argued that large tracts of conserved lands may restrict local employment opportunities by reducing the opportunities for extractive industries, while also potentially inducing in-migration of amenity seeking residents.…”
Section: Background and Hypotheses Arising From Related Literaturementioning
confidence: 99%
“…The reverse was detected for climatically more favourable sites: a higher number of sunny days is associated with lower earnings. In the US, favourable climatic conditions are robust predictors of population growth, rising house prices (Rappaport 2007), real wages and interstate migration (Huffman and Feridhanusetyawan 2007). These findings might not be completely transferable to Germany: Arntz (2010) detected only a modest relevance of amenities.…”
Section: Mobility Premiums As Location-specific Differentialsmentioning
confidence: 99%